Rechallenge and retreatment with topical imiquimod 5% in transplant recipients: A multicenter experience on actinic keratoses and basal cell carcinomas - Paolo Fava; Gabriele Roccuzzo; Nicole Macagno; Francesco Cavallo; Valentina Celoria; Gianluca Avallone; Elisa Zavattaro; Federica Veronese; Luigi Biancone; Paola Savoia; Pietro Quaglino (Wiley, 2024)
Abstract Background Solid organ transplant recipients (SOTRs) have an increased risk of developing non melanoma skin cancers (NMSCs). The use of Imiquimod, a toll‐like‐receptor agonist, is still debated in SOTRs. Objectives The aim of this study was to evaluate efficacy and safety of topical Imiquimod in two Dermatology Centres for skin cancers in SOTRs. Methods All SOTRs with age > 18 and a dermoscopic diagnosis of superficial basal cell carcinoma (BCC) and/or actinic keratose (AK), annually followed up between January 2022 and December 2022 were screened. Results 80 NMSCs (41 BCC and 39 AK) in 66 SOTRs were identified and treated. 57 (86.4%) were male. The mean age was 66.2 years (30−85). 60 patients (90.1%) had transplanted kidney, 1 (1.5%) lung, 3 (4.5%) liver, and 1 (1.5%) heart. The average time since first transplant was 17 years (3−40 years). Tacrolimus, steroids, and mycophenolate mofetil were the most frequently used immunosuppressants (71%; 67.7%; 53.2% of cases, respectively). Responses to the first course of treatment were CR in 64.3% of cases (53.6% in AK; 67.7% in BCC); PR in 28.6% of cases (42.9% in AK; 12.9% in BCC); NR in 12.5% of cases (3.6% in AK; 19.4% in BCC). Fourteen patients received a second course of imiquimod for a persistent lesion (1 AK, 4 BCC) or a new lesion (4 AK, 5 BCC). Responses to the second course of treatment were observed in 4 (80%) and 7 (78%) cases in the persistent and new lesion, respectively (p = 0.34). No systemic adverse events were noted. The main side effects were mild: erythema, scales, and crusts, itching, or pain. Conclusions Topical imiquimod represents a viable and safe option in this category of patients. The response to imiquimod in subjects who have had more than one cycle is not related to the response to previous treatments but rather to the intrinsic characteristics of the lesion.